IMPLEMENTATION OF SURVIVAL ESTIMATION OF BONE MARROW TRANSPLANT PATIENTS WITH SEMIPARAMETRIC HAZARD FUNCTION USING MINITAB SOFTWARE - Hanung Prasetyo; Ferra Arik Tridalestari; Wawa Wikusna (Informatika, Universitas Jenderal Soedirman, 2022)
The Hazard Rate probability value estimation method is an estimation model that is carried out fully parametrically or it can also be done by non-parametric methods. Sometimes using the parametric method will give biased value results because it gives too much value in general, while the non-parametric estimation method causes the variance value to be too high. Therefore, for some cases there is a way to combine the two methods, which is called the Semiparametric method, which is an estimation method that has the characteristics of improving non-parametric parametric estimates. This paper shows that the semiparametric hazard method gives better results than parametric and non-parametric methods. The basis for developing the semiparametric probability method is to roughly estimate the probability of a parametric conjecture as a first step and then proceed with several correction models for setting data. The implementation of the probability value in this study uses the Life Time data of Transplant bone patients at Hospital X with the help of Minitab software analysis.